Synthesis and Analgesic Effects of Methoxy-Pyrrole Derivative of Phencyclidine on Mice - Ahmadi, Abbas; Solati, Jalal; Hajikhani, Ramin; Pakzad, Sara (Asian Journal of Chemistry, 2011)
Phencyclidine, 1-[1-phenylcyclohexyl]piperidine (PCP, I) and its derivatives have shown considerable pharmacological effects. In this work, pyrrole derivative of phencyclidine (PCPpyrrole, 1-[1-phenylcyclohexyl]pyrrole, II) and a new derivative (1-[1-[3-methoxyphenylcyclohexyl] pyrrole, III) and their intermediates were synthesized, then the acute and chronic pains were examined on mices at 1 mg/kg dosage using tail immersion (as a model of acute thermal pain) and formalin (as a model of acute chemical and chronic pain) tests and the results were compared with phencyclidine and control (DMSO) groups. The results indicated that III produced more analgesic effects compared to II in tail immersion test and also revealed that the newly synthesized derivative (III) significantly reduced chronic pain (especially in initial of phase II) in formalin test compared to other groups.